Pengaruh Pelayanan, Fasilitas Perpustakaan dan Kinerja Pustakawan Terhadap Kepuasan Pengguna pada Perpustakaan Pusat Negeri Semarang (Universitas Negeri Semarang, 2021)
The purpose of this study was to obtain empirical evidence of the influence of services, library facilities and librarian performance on user satisfaction at the Central Library of the State University of Semarang. The population in this study were all visitors to the UNNES Central Library as many as 116 people with incidental sampling technique. Data collection methods used in this study, namely using a questionnaire, observation and documentation. Analysis of the data using descriptive analysis of percentages and multiple linear regression. The results showed (1) simultaneously service, library facilities and librarian performance had an effect on user satisfaction at the Central Library of the State University of Semarang which was 45.1%, (2) partially the service had an effect on user satisfaction at the Central Library of the State University of Semarang of 12.81. %, (3) library facilities have an effect on user satisfaction at the Central Library of Semarang State University by 39.18%, (4) and librarian performance has an effect on user satisfaction at the Central Library of Semarang State University by 49.98%.